Roma fiatalok a munkaerőpiac kapujában = Young Romanies at the gate of labour market - Miklós, Péter (Közép-Európai Közlemények, 2017)
The presence of the romany population in Hungary in the world of education and the World of work fluctuated greatly in the twentieth century. While in the age of state-socialism the employment rate of romanies was very high in Hungary, it dropped dramatically after the change of régimé (1989/1990). In the higher education levels - and especially in colleges and universities - romany students are disproportionally underrepresented. There are several reasons fór this, mostly the negative mechanism of educational segregation. Recently, governmental and civil endeavors have also emerged to eliminate segregation and increase the presence of romany students in higher education. After the educational opportunities, the road to the labor market will be opened.